IT architecture flexibility and IT governance decentralisation as drivers of IT-enabled dynamic capabilities and competitive performance: The moderating effect of the external environment. Issue 5 (3rd September 2021) - Mikalef, Patrick; Pateli, Adamantia; van de Wetering, Rogier
ABSTRACT: A question of central importance for researchers and practitioners is how information technology (IT) can help firms survive and thrive in turbulent and constantly changing business environments. To address this issue, this study develops the idea that IT architecture flexibility helps sustain competitive performance by driving the formation of IT-enabled dynamic capabilities, and that IT governance decentralisation strengthens this relationship. IT architecture flexibility and IT governance decentralisation, therefore, develop complementary effects. We argue that IT-enabled dynamic capabilities are a core antecedent for competitive performance gains, particularly under uncertain external environmental conditions. Tests of the proposed model using survey data from 322 international firms support these ideas. Our research also shows that, under conditions of high environmental heterogeneity, the value of IT architecture flexibility and IT governance decentralisation is increased, while the impact of IT-enabled dynamic capabilities on competitive performance is amplified.